A minimally invasive model data passing interface for integrating legacy environmental system models. (June 2016) - Dozier, A.Q.; David, O.; Arabi, M.; Lloyd, W.; Zhang, Y.
Abstract: This paper presents the Model Data Passing Interface (MODPI). The approach provides fine-grained, multidirectional feedbacks between legacy environmental system models through read and write access to relevant model data during simulation using a bidirectional, event-based, publish-subscribe system with a message broker. MODPI only requires commented directives in the original code and an XML linkage file with an optional custom data conversion module. Automated code generation, compilation, and execution reduce the programming burden on the modeler. Case study results indicated that MODPI required less code modifications within each model code base both before and after automated code generation, outperforming a baseline subroutine approach. Performance overhead for MODPI was minimal for the use case, offering speedup in some cases through parallel execution. MODPI is much less invasive than other techniques, potentially encouraging adoption by the modeling community in addition to maintainability and reusability of integrated model code. Graphical abstract: Highlights: We developed a minimally invasive model data passing interface. MODPI requires very minimal modifications to original model code bases. MODPI uses code generation to minimize the programming work. MODPI provides fine-grained, multidirectional feedback between models. We provide analysis of computational overhead concerns.